Mathematical modelling of seepage through dam - Ting, Huong Yun. (2013)
The boundary element method is studied and applied to investigate the problem of water seepage through dam which requires the determination of the location of a surface. The seepage free surface is obtained iteratively by a corrector-predictor approach based on the boundary element method. Several specific cases of the problem are studied in detail. The result for each case study is plotted by using MATLAB program. Numerical results obtained show satisfactory agreement with those published in the literature. The applicability of the method is evaluated based on comparison with other numerical solutions. More complicated cases involving dams with toe drains for better seepage control are also investigated in this project.